Degradation of Building Materials by Corrosive Pollutants - Rajesh Kumar Singh; Pankaj Kumar Singh; Deepmala Kumari (International Journal of Minerals, 2025)
Fiber reinforced polymers (FRP) is used for the corrosion suppression of reinforced concrete structures (RCS). One of the main issues with reinforced concrete constructions is corrosion. It interacts with acids, alkalis and salts to produce disintegration in building materials components. Pollutants and effluents speed up disbanding inside and outside reinforced structures. Bio-wastes come in contact of building materials to develop miro and macro-organism and these organisms release acid substances to accelerate corroding effect. Hostile agents like acid rain, greenhouse gases, global warming, heat waves, climate change, humidity and moisture also create deformation in building block components. Sea weather has availability of chloride ions to corrode iron bar in reinforced concrete. Building materials corrosion enhance due to increase atmospheric temperature. Particulates aggravate corrosion of building materials. Corrosive substances attack on interface of reinforced structures and some enter inside osmosis or diffusion process thus chemical, biochemical and electrochemical occurs among them. Rebar steel corrodes in such ambient environment and develop various form corrosion like galvanic, pitting, crevice, stress, intergranular, blistering, embrittlement, erosion, cavitations etc. It produces disbanding between rebar steel and concrete. Some gases absorb moisture to exhibit swelling and dissolving corrosion on the surface concrete structures. Corrosion reactions alter physical, chemical and mechanical properties of building block components and tarnish facial appearance. The fiber reinforced polymers used to control corrosion reinforced concrete. Developed countries spend 4% of their gross national product on corrosion prevention, part replacement, and upkeep. The primary sources of corrosive substances include mining, thermal power plants, petroleum refineries, burning fossil fuels, chemical wastes, biological wastes, human wastes, household wastes, agricultural wastes, animal wastes, food grain wastes, hospital wastes, chimney flue gases, and industrial effluents. As effluents, these sources emit acids, alkalis, salts, organic compounds, metals, carbon oxides, nitrogen oxides, sulfur oxides, halogen oxides, sulfur hydride, nitrogen hydride, volatile organic compounds as flue gases, and various wastes. Water, air, and soil are all contaminated by these toxins. The fundamental building elements for R C structures include sand, stones, cements, iron bars, bricks, and water. The corrosive compounds listed above create an unfavorable environment for building materials. This corrosive impact shortens the life of RC structures and causes internal and external disintegration, raising doubts about their stability, lifespan, and durability. RC structures can be protected from corrosion using a variety of methods. However, these methods did not provide them with adequate protection. Therefore, fiber-reinforced polymers will be used in this effort to control RC structure corrosion.
Keywords: Acid rain; Building materials; Effluents; Flue gases; Pollutants; R C structures and Fiber Reinforced Polymers; Weather; wastes